PENDIDIKAN GIZI DAN PENCEGAHAN STUNTING BAGI BALITA DI DESA KAPOPO - Budimah; Ananda Aisyah; Mubayyin, Afief (Sambulu Gana : Jurnal Pengabdian Masyarakat, 2025)
Stunting is a global health issue that has a significant negative impact on a country. Community empowerment through the role of posyandu cadres and mothers with toddlers is very much needed in efforts to prevent stunting. The aim of this activity is to provide health education about stunting and providing proper nutrition for children under five. This activity was carried out on September 6 2024 at Posyandu Toddlers RW 02 with a target of 3 posyandu cadres and 8 mothers with toddlers posyandu cadres and mothers with toddlers. Health workers together with toddler posyandu cadres are expected to be able to provide education to the public about stunting and proper nutrition for toddlers as an effort to prevent stunting which is carried out regularly at least 3 times a month.